2021
DOI: 10.4314/bajopas.v13i1.15
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and antibacterial screening of leaf extracts from Cassia singueana Del.(Fabaceae)

Abstract: No Abstract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…This also concurs with a report by Kareru et al [ 27 ], which showed that the aqueous leaf extracts of S. singueana had higher effects on S. aureus and B. subtilis than it had on E. coli . This is also in agreement with Jibril et al [ 64 ] who demonstrated the broad-spectrum antibacterial effects of methanol and ethyl acetate leaf extracts of S. singueana . However, our findings are partly contrary to the reports of Shawa et al [ 20 ], which suggested that aqueous leaf and root extracts of S. singueana were inactive on S. aureus and Pseudomonas aeruginosa .…”
Section: Discussionsupporting
confidence: 93%
“…This also concurs with a report by Kareru et al [ 27 ], which showed that the aqueous leaf extracts of S. singueana had higher effects on S. aureus and B. subtilis than it had on E. coli . This is also in agreement with Jibril et al [ 64 ] who demonstrated the broad-spectrum antibacterial effects of methanol and ethyl acetate leaf extracts of S. singueana . However, our findings are partly contrary to the reports of Shawa et al [ 20 ], which suggested that aqueous leaf and root extracts of S. singueana were inactive on S. aureus and Pseudomonas aeruginosa .…”
Section: Discussionsupporting
confidence: 93%
“…Four tetrahydroanthracene derivatives which showed significant antibacterial and antiplasmodic activity namely singueanol-I and -II, torosachrysone and germichrysone have been previoulsy isolated from the roots of S. singueana (34). Other compounds which have been isolated from S. singueana include stigmasterol, stigmast-4-en-3-one, stigmast-4,22-dien-3-one, 1-heneicosanol, and hexyl heneicosanoate from the n-hexane leaf extract (35). The flavanoid, luteolin has also been isolated from this plant species previously (36).…”
Section: Discussionmentioning
confidence: 99%
“…The C. singueana extract exhibited appropriate values for phenolic content (120.01 mg GAE/g dry extract), DPPH (IC50: 9.35 μg/mL), and α-glucosidase inhibition (I%: 90.47%) (17). In a phytochemical screening performed on the methanolic extract of C. angustifolia root and its fractions, the hexane fraction showed qualitative amounts of terpenoids, anthraquinones, and coumarins (18).…”
Section: Discussionmentioning
confidence: 99%
“…C. sieberiana exhibited significant activities for 15-LOX inhibition (80.93% inhibition) and FRAP (2120 μmol Fe2+/g dry extract). The extracts of C. singueana and C. sieberiana contain αglucosidase inhibitors, antioxidants, and antiinflammatory compounds, making them useful for the treatment of ulcers and diabetes (17).…”
Section: Discussionmentioning
confidence: 99%